A SWOT ANALYSIS OF THE LANGUAGE POLICIES IN EDUCATION IN KENYA AND ETHIOPIA (The University of Nairobi Journal of Language and Linguistics, 2023)
This paper compares the language policies in education (past and present) inEthiopia and Kenya. It shows the role played by both international andindigenous languages, e.g. as languages of instruction in education in eithercountry. Multilingualism is reflected in a different way in the education systemof either country, as Ethiopia has over eighty languages, while Kenya has aboutforty-two. An analysis of Strengths, Weaknesses, Opportunities and Threats (i.e.a SWOT analysis) of the language policies in education in the two countries iscarried out with a view to showing how each can be improved in their respectivemultilingual settings. In the specific case of language policies in Kenya andEthiopia, the aim of a SWOT analysis is to help those concerned with them tothink of a language policy in education that may strengthen the position ofindigenous languages, so that these can coexist on an almost equal footing withthe dominant languages of education. The main strength seen in the languagepolicy in education in Kenya is the introduction of Kiswahili as a compulsorysubject both in primary and secondary school. For Ethiopia, a major strength ofits current language policy is the promotion of many indigenous languagesthrough education, since some of them are learnt as school subjects. Morerelevantly, primary school education is conducted in the vernacular. A majorweakness of the educational policy in Kenya is that none of the indigenouslanguages, apart from Kiswahili, is taught as a subject, while in the case ofEthiopia a major weakness is that a solid mastery of English is lacking, yet it isthe medium of instruction for secondary and higher education. With regard toopportunities, both countries have an opportunity to develop all languages byhaving them in written form. In this connection, more elementary books formother tongue education could be prepared for both big and small languages. Inboth countries, the only threat to the use of the mother tongue in education isthe negative attitude of parents, teachers and students towards it.